A Feasible Laboratory-Strengthening Intervention Yielding a Sustainable Clinical Bacteriology Sector to Support Antimicrobial Stewardship in a Large Referral Hospital in Ethiopia - Yansouni, Cedric P.; Seifu, Daniel; Libman, Michael; Alemayehu, Tinsae; Gizaw, Solomon; Johansen, Øystein Haarklau; Abebe, Workeabeba; Amogne, Wondwossen; Semret, Makeda (Frontiers in Public Health, 2020)
Background: Access to clinical bacteriology in low resource settings (LRS) is a key bottleneck preventing individual patient management of treatable severe infections, detection of antimicrobial resistance (AMR), and implementation of effective stewardship interventions. We sought to demonstrate the feasibility of a practical bundle of interventions aimed at implementing sustainable clinical bacteriology services at Tikur Anbessa Specialized Hospital in Addis Ababa, Ethiopia, and report on cost and intensity of supervision. Methods: Starting in Dec 2015, an intervention based on the CLSI QMS01-A guideline was established, consisting of (i) an initial needs assessment, (ii) development of key standard operating procedures, (iii) adaptation of processes for LRS, (iv) training and supervision of laboratory staff via consultant visits and existing online resources, and (v) implementation of a practical quality systems approach. A guiding principle of the bundle was sustainability of all interventions post implementation. Outcomes and challenges: An initial investment of US 26,200 for laboratory reagents, and a total of 50 visit-days per year from three Canadian and Norwegian microbiologists were committed. Twelve SOPs, including antimicrobial susceptibility testing, were adapted, and an automated blood culture platform was donated (bioMerieux). In the first 18 months of implementation of the intervention, the average volume of specimens analyzed in the lab went from 15/day to 75/day. The number of blood cultures tested increased from an average of 2/day to over 45/day. Antimicrobial susceptibility testing was introduced and cumulative antibiograms were generated for the institution. Quality control was implemented for all procedures and quality assurance tools implemented included external quality assurance and proficiency testing of six technologists with longitudinal follow-up. The laboratory is on the path toward SLIPTA accreditation by the African Society for Laboratory Medicine. Reagent costs, staff training and retention, and engagement of clinical personnel with the lab proved to be manageable challenges. Key external challenges include in-country supply-chain management issues, lack of competition among distributors, and foreign-currency exchange distortions. Conclusions: Using a relatively low-intensity intervention based on existing training tools and accreditation schemes, we demonstrate that establishment of reasonable-quality clinical bacteriology is not only within reach but also a critical step toward assessing the burden of AMR in settings like this one and implementing effective stewardship strategies.